2006
DOI: 10.1148/radiol.2381041765
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-Phase Dynamic CT Enhancement as a Prognostic Factor for Mass-forming Intrahepatic Cholangiocarcinoma

Abstract: The degree of enhancement on delayed-phase CT scans is a useful indicator for prediction of the prognosis of patients with mass-forming ICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
86
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 18 publications
10
86
2
2
Order By: Relevance
“…In other reports, hypovascularity or delayed enhancement have been associated with poor survival [34,43], agreeing with the present results.…”
Section: Nanashima Et Al Page 10supporting
confidence: 94%
See 1 more Smart Citation
“…In other reports, hypovascularity or delayed enhancement have been associated with poor survival [34,43], agreeing with the present results.…”
Section: Nanashima Et Al Page 10supporting
confidence: 94%
“…Yamamoto et al reported that peripheral mass-forming ICC mimics the clinical characteristics of HCC, including imaging findings [42]. Mass-forming-type ICC with high vascularity may show HCC-like characteristics, but with significant differences in enhancement pattern and tumor morphology [43]. Larger tumor size or lower degree of histological differentiation were related to the classical hypovascular ICC.…”
Section: Nanashima Et Al Page 10mentioning
confidence: 99%
“…It was confirmed that CT and/or MRI findings of ICC were correlated with pathological findings; that is, the hyperenhancing areas always indicated a large number of tumour cells and the areas of delayed enhancement corresponded to fibrotic stroma at pathological examination. In addition, different morphological subtypes tended to exhibit distinct enhancement characteristics on CT [7,8,[11][12][13]. On CEUS, besides the specific feature of peripheral rim-like hyperenhancement, diverse imaging findings of ICC were reported [9,10,[14][15][16][17].…”
mentioning
confidence: 99%
“…The imaging features of ICC have been reported by many researchers (3,4). Most of these focused on imaging characteristics in relation to the internal desmoplastic change.…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese Liver Cancer Group has classified ICCs into three types: mass-forming, periductal-infiltrative, and intraductal (1). The mass-forming type of intrahepatic cholangiocarcinoma (mICC) is the most common (60% of all ICCs) (2) and can show various imaging findings on dynamic computed tomography (CT) or magnetic resonance imaging (MRI) using extracellular contrast agent (3,4). Regardless of the findings on the arterial phase, delayed temporal contrast enhancement is a typical feature of ICC because of the distribution of extracellular contrast into intratumoral fibrous stroma (5).…”
mentioning
confidence: 99%